Students’ and Lecturers’ Problems in Online Learning Speaking Class - Gusmuliana, Paidi; Kusumawati, Citra; Prihantoro, Prihantoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aimed at finding; Students’ and lecturers’ problems in online learning speaking class and the efforts to cope with the problems. This study used a qualitative research design by using interviews as the encouragement of the data. The research subjects were 5th semester 2020/2021 students and speaking lecturers of the English language education Department in IAIN Curup. Based on the results of this study, the researcher found the problems that students face during online learning, were; network problems, lack of confidence, shyness and lack of motivation, worrying about grammatical and pronunciation errors, and difficulty understanding the material. Besides, the efforts of students were finding a good network, fixing problems with the platform used during online classes, and they asked for creative classes, and using their learning style to understand the material being studied to overcome their learning difficulties. For lecturers’ problems in online learning, speaking class are difficulty to apply teaching strategies such as pair and group work, lack of ICT ability, and also the problems come from the student, and lecturer’s efforts such as preparing anticipation application, sharing with their colleagues and always give students motivation. So, the problems of the students and lecturers were in teaching strategies and problems that come from the students themselves. So, the efforts increase motivation in practicing online learning and creative learning is needed.